A rare case report of type IV capitellum fracture in a young female managed by a single Herbert screw fixation - David, Vivek Kumar; Kumar, Abhishek; ., Chittra (International Journal of Research in Orthopaedics, 2020)
Isolated coronal shear fractures of capitellum are very rare, accounting for nearly 1% of all elbow fractures. There are various approaches and implants documented for management of such fractures. One of them is lateral Kocher’s approach and Herbert screw fixation. Our case report is strengthening this approach and Herbert screw fixation and shows good short term functional outcome along with radiological union.